2017
DOI: 10.1130/abs/2017am-308401
|View full text |Cite
|
Sign up to set email alerts
|

Detrital Zircon Typology and U/Pb Geochronology for the Miocene Ladrilleros-Juanchaco Sedimentary Sequence, Equatorial Pacific (Colombia): New Constraints on Provenance and Paleogeography in Northwestern South America

Abstract: FIGURE 1. A) Location of the Ladrilleros-Juanchaco Sedimentary Sequence (LJSS) on the Colombian and South American context on the Paci c coast. B) Local geological framework of the LJSS (modi ed from Montoya, 2003). C) General aspect of outcrops for the LJSS in the studied section, NW-SE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Heavy mineral and U-Pb zircon provenance can be complemented by the typological analysis of zircon populations (Konsa and Puura, 1999;Capuzzo and Bussy, 2000;Anani et al, 2012;Osorio-Granada et al, 2017). The morphology of this ubiquitous, refractory mineral is controlled by temperature and chemical conditions during crystallization (Pupin, 1980), making it useful for tracking the different igneous rock types present in source regions (Dabard et al, 1996;Anani et al, 2012).…”
Section: Anh-tierraltamentioning
confidence: 99%
“…Heavy mineral and U-Pb zircon provenance can be complemented by the typological analysis of zircon populations (Konsa and Puura, 1999;Capuzzo and Bussy, 2000;Anani et al, 2012;Osorio-Granada et al, 2017). The morphology of this ubiquitous, refractory mineral is controlled by temperature and chemical conditions during crystallization (Pupin, 1980), making it useful for tracking the different igneous rock types present in source regions (Dabard et al, 1996;Anani et al, 2012).…”
Section: Anh-tierraltamentioning
confidence: 99%
“…There have only been few studies that used this features for detrital settings (e.g. Dunkl and Demény 1997;Naing et al 2014;Osorio-Granada et al 2017). In the case of Namibian modern sands there is a narrow array of zircon morphotypes in the south with highest amounts for the S24 (Fig.…”
Section: Remarks On Zircon Morphologymentioning
confidence: 99%
“…For different rock types including magmatic, metamorphic, and sedimentary rocks, zircon grains developed into various crystal shapes due to different crystallization environment conditions such as temperature, pressure, pH value, oxygen fugacity, and so on [40,41]. Previous studies demonstrated that zircon is featured by slender crystals in high-level granites and acid volcanic rocks, but its crystal shapes generally are characterised by stunted and stubbed shapes in the sedimentary and low-grade metamorphic rocks [40][41][42]. Thus, the elongation of zircon grains that are not too round is always used as an index to reflect the crystallisation velocity and temperature [43,44].…”
Section: Sediment Provenance Of the Yangtze Delta In The Pliocenementioning
confidence: 99%